2011
DOI: 10.1021/jo2019653
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Applications of Potential Substitutes of t-Bu-Phosphinooxazoline in Pd-Catalyzed Asymmetric Transformations and Their Use for the Improvement of the Enantioselectivity in the Pd-Catalyzed Allylation Reaction of Fluorinated Allyl Enol Carbonates

Abstract: The design, synthesis, and applications of potential substitutes of t-Bu-PHOX in asymmetric catalysis is reported. The design relies on the incorporation of geminal substituents at C5 in combination with a substituent at C4 other than t-butyl (i-Pr, i-Bu, or s-Bu). Most of these new members of the PHOX ligand family behave similarly in terms of stereoinduction to t-Bu-PHOX in three palladium-catalyzed asymmetric transformations. Electronically modified ligands were also prepared and used to improve the enantio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“… 387 From the latter, precursors of medicinally relevant hydroxymethyl- cis -1,3-cyclopentenediol building blocks were synthesized ( Scheme 113 ). Paquin’s group used this strategy to synthesize α-allylated α-fluoroketones (for analogous decarboxylative transformations see section 3.1 )., 388 389 …”
Section: Asymmetric Allylic Substitutionmentioning
confidence: 99%
“… 387 From the latter, precursors of medicinally relevant hydroxymethyl- cis -1,3-cyclopentenediol building blocks were synthesized ( Scheme 113 ). Paquin’s group used this strategy to synthesize α-allylated α-fluoroketones (for analogous decarboxylative transformations see section 3.1 )., 388 389 …”
Section: Asymmetric Allylic Substitutionmentioning
confidence: 99%
“…To our pleasure, cinchonidine derived squaramide catalyst C4 enabled the reaction to furnish 3a in up to 76% ee with 69% yield, albeit with prolonged reaction time (entry 4). Then we examined solvent effects to improve the reactivity and enantioselectivity (entries [5][6][7][8][9][10][11][12]. While the use of toluene, CH 2 Cl 2 , THF, EtOAc, and MeCN all led to low ee values, alcoholic solvents proved to be capable of enhancing the enantioselectivity, and trifluoroethanol (TFE) turned out to be the best in terms of enantioselectivity and reactivity, as the reaction could finish within 1 d to afford the desired product 3a in up to 77% yield and 86% ee (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…Monofluorinated silyl enol ethers 2, as readily available α-fluorinated enolate precursors, have received growing attention for the diversity-oriented synthesis of chiral α-fluoroketones. [9] The past decade has witnessed a variety of elegant protocols based on m-FSEEs, including allylation, [10] arylation, [11] aldol, [12] Michael [13] and Mannich reaction, [14] as well as olefination. [15] Since the Paquin group pioneered a Pd-catalyzed enantioselective allylation reaction of m-FSEEs 2 in 2007, [10a] m-FSEEs have found increasing application in asymmetric catalysis.…”
Section: Scheme 1 Known Synthetic Strategies and This Workmentioning
confidence: 99%
“…[82] Paquin and co-workers later demonstrated that this reaction also occurs with the palladium complex of the substituted i-Pr-PHOXtype ligand L28,which is more readily available,with similar outcome. [83] One year later, Paquin reported the asymmetric decarboxylation of allyl a-fluoro enol carbonates in the presence of ap alladium complex of t-Bu-PHOX ligand L24 (Scheme 49). [84] As was observed for other decarboxylative allylations,these reactions proceeded with high enantioselectivities with cyclic,b ut not acyclic,s ubstrates.U nlike decarboxylative allylations of nonfluorinated enol carbonates, these reactions required high metal:ligand ratios to proceed with high enantioselectivity (4:1 Pd:L results in 96:4 er;1 :1 Scheme 45.…”
Section: Allylic Substitutions Of Unstabilized A-fluoro Enolatesmentioning
confidence: 99%